(untitled) (Research, Society and Development, 2020)
Objective: To identify, through the literature, the main risk factors that influence the increase of HIV / AIDS cases in the elderly population. Method: An integrative literature review was performed through the databases: BDENF, INDEX, LILACS and MEDLINE, in the months of March and April of 2019, using the descriptors Health of the Elderly; Sexually Transmitted Diseases; HIV; Acquired Immunodeficiency Syndrome; Nursing. Results and Discussion: A total of 13 articles were included, highlighting the vulnerability of the elderly to exposure to HIV / AIDS, lack of knowledge and unpreparedness of health professionals, as well as the lack of HIV-related public policies / AIDS in the third age. Conclusion: It was possible to identify that the role of Nursing is of great relevance to the understanding of the elderly in relation to HIV / AIDS, and health education should be consistently covered, since the main justification is the lack of information on the part of this population.